IMPLEMENTASI ISLAMIC SERVICE QUALITY DALAM MENINGKATKAN KEUNGGULAN KOMPETITIF: STUDI KASUS PELAKU USAHA BIRO PERJALANAN UMROH DI SURABAYA - Rosmiati, Rosmiati; Hasan, Nurul Fatma (Investama : Jurnal Ekonomi dan Bisnis, 2024)
This study aims to analyze how the implementation carried out by Umrah travel agency business actors in Surabaya in increasing competitive advantage through sharia-based service quality. Thus, it is hoped that this research can produce useful recommendations for improving service quality, especially in the context of service quality in accordance with sharia principles. The methodology used in this research uses qualitative methods with primary data sources obtained through observation and interviews. The object of this research is the business actors of the Umrah travel agency in Surabaya in implementing Islamic Service Quality. Respondents selected from each company are the Main Department of the company, as well as company management who are responsible as Operations and Marketing Managers, and Administrative CS staff, so that they are considered relevant to answer the objectives of this study, while secondary data is obtained from literature studies. The results of this study indicate that Islamic Service Quality in three Surabaya Umrah travel companies, each company has different advantages and approaches in applying Islamic service quality principles, which are divided into six main indicators, namely, Compliance, Assurance, Reliability, Tangible, Empathy, and Responsiveness.